"Is Your Man Stepping Out?" An Online Pilot Study to Evaluate Acceptability of a Guide‐Enhanced HIV Prevention Soap Opera Video Series and Feasibility of Recruitment by Facebook Advertising. (July 2015) - Jones, Rachel; Lacroix, Lorraine J.; Nolte, Kerry
Abstract : N/A: Love, Sex, and Choices (LSC) is a 12‐episode soap opera video series developed to reduce HIV risk among at‐risk Black urban women. We added a video guide commentator to offer insights at critical dramatic moments. An online pilot study evaluated acceptability of the Guide‐Enhanced LSC (GELSC) and feasibility of Facebook advertising, streaming to smartphones, and retention. Facebook ads targeted high‐HIV‐prevalence areas. In 30 days, Facebook ads generated 230 screening interviews: 84 were high risk, 40 watched GELSC, and 39 followed up at 30 days. Recruitment of high‐risk participants was 10 per week, compared to seven per week in previous field recruitment. Half the sample was Black; 12% were Latina. Findings suggest GELSC influenced sex scripts and behaviors. It was feasible to recruit young urban women from a large geographic area via Facebook and to retain the sample. We extended the reach to at‐risk women by streaming to mobile devices.